Temperature-dependent electronic structure of nickel metal - Kreutz, T. J.; Greber, T.; Aebi, Philipp; Osterwalder, J. (My University, 1998)
An extended set of temperature-dependent ARUPS data from Ni(111) is presented. The ferromagnetic and the paramagnetic state as well as the phase transition are examined in great detail. Rather new and unconventional modes of data acquisition in ARUPS are applied with high angular and energy resolution, exhibiting great power near the Fermi energy EF. Even up to 5kBT above EF energy bands are readily observed. The understanding of these ARUPS data is strongly enhanced by spin-polarized band structure calculations. Exchange-split bands of both, sp- and d-character, are resolved in angular scans and in photoemission Fermi-surface maps. From two-dimensional data sets in energy and angle the dispersion and the exchange splitting are obtained with high precision. All the observed sp- and d-bands clearly exhibit a Stoner-like collapsing-band behavior. The exchange splitting ΔEex vanishes above TC in all cases, and ΔEex closely follows the temperature dependence of the macroscopic magnetization. The apparent deviations from the Stoner-like band behavior stated in P. Aebi et al. , Phys. Rev. Lett. 76, 1150 (1996) are explained. Furthermore we detect anomalously high intensity from a minority d-band close to an sp-band. This strongly suggests that sp-d-fluctuations at the Fermi level are a driving force for the magnetic phase transition of nickel.